Transitional Cell Carcinoma: A Case Report with Clinical, Histological and Cytological Findings - Anureet Kaur (Journal of Clinical and Diagnostic Research, 2013)
Papillary carcinoma of the uterine cervix with features reminiscent of Transitional Cell Carcinoma (TCC) of urothelial origin, is a poorly recognized subtype of cervical carcinoma. This tumour has a propensity for late metastasis and local recurrence, in spite of the fact that histologically it could be misinterpreted as CIN grade III with a papillary configuration or as a squamous cell papilloma. This tumour occurs mainly in post-menopausal females, it is potentially aggressive and it presents at a more advanced stage. Here, we are presenting a case of a 65-year-old female who presented with post-menopausal bleeding and pelvic pain, and underwent hysterectomy for pyometra. The cervix showed a focus of papillary transitional carcinoma.